The Effect of E-Service Quality, Perceived Value, Customer Satisfaction on Willingness to Pay Spotify Premium App in Indonesia - Fariza Altruista Pramadani; Anas Hidayat (Cita konsultindo, 2025)
This study aims to analyse the influence of E-Service Quality, Perceived Value, and Customer Satisfaction on Willingness to Pay. The population for this study consists of individuals in Indonesia who use the Spotify Premium application. The sample includes 240 respondents, all aged 17 and above, who use Spotify Premium and are distributed across Indonesia. Questionnaires were used to collect the data needed for the research. The analysis method employed is Structural Equation Modelling (SEM) using AMOS version 24.0. The results of this study indicate that E-Service Quality positively influences Customer Satisfaction, Perceived Value positively influences Customer Satisfaction, E-Service Quality positively influences Willingness to Pay, Perceived Value positively influences Willingness to Pay, and Customer Satisfaction positively influences Willingness to Pay.